Effects of streptomyces rochi Biosurfactants on Pathogenic Staphylococcus aureus and Pseudomonas aeruginosa - Al-Healy, Nadia H.; Al-Sammak, Essra Gh. (Al-Mukhtar Journal of Sciences, 2022)
Fifty soil samples were collected from soils contaminated and uncontaminated with hydrocarbons. Six isolates belonging to Streptomyces rochei were diagnosed, 8% from contaminated soil and 6% from uncontaminated soil. Isolates were diagnosed depending on the study of 16s rDNA compared to standard isolates within the National Center for Biotechnology Information site. 28 smears of wounds and 12 smears of burns were collected, including Staphylococcus aureus isolates (35.7%) and Pseudomonas aeruginosa (16.6%). The isolates of Staphylococcus aureus and Pseudomonas aeruginosa showed multiple resistance to antibiotics, Oxacillin, Erythromycin, Nalidixic acid, and Tetracycline. Isolate Streptomyces rochei 19 showed the ability to produce biosurfactants that have antagonistic properties against Staphylococcus aureus and Pseudomonas aeruginosa. In addition, the biosurfactant production from Streptomyces rochei 19 were non-toxic to the potential growth of Brassica oleracea seeds at 1.5 and 50 mg/cm3. The biosurfactant was diagnosed as Lipopeptide using thin layer chromatography and GC-Mass technique.